Developing MATMINO (Domino Mathematics) Learning Media in Grade 7 Algebra Material - Sri Wahyuningtyas; Leonard Leonard; Natalia Tri Astuti (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2021)
Math Domino Learning Media game is developed to meet the needs of students, because it has not been the availability of learning media to help the process of learning mathematics. The research aims to determine the existence of learning media to improve the development of game media through the learning media of Domino math game, the feasibility of Domino math learning. The subjects of this study were 7 th grade students of JHS 209 Jakarta which consisted 25 students. This research type is Research Development (R&D) with ADDIE model. This watchfulness consists of several steps, namely: (1) Analysis, (2) Design, (3) Development, (4) Implementation, (5) Evaluation. Validity test was done by 6 validators. Based on the results of research, it can be concluded that development of learning media MATMINO can be used on mathematics subjects The results show that the average gained from material experts is 4,33 (very decent) and the average gained by media experts is 4,37 (very decent). Student's response to learning media of MATMINO in very good category with 4.33 average score. Based on these results it is stated that domino mathematics learning media on algebra material can be used in the process of learning mathematics activities.